Of sinners and saints - Soriquez, Ruben Maria, 1971-; Soriquez, Ruben Maria, 1971-; Ramos, Alejandro Mirasol; Bagatsing, Raymond (See Thru Pictures, 2014)
Leonardo is an Italian missionary who counsels battered women and teach poor children in the Philippines. But problems arise when he meets Merlinda, a young woman with a violent husband and a 6 year old missing child. --